Synthesis of Cytogenin Analogues by C(sp2)–H Functionalization under Ruthenium(II) Catalysis, and DFT Analysis - Joshi, Ashish; Chavada, Lilesh Rambhai; Choudhary, Mridula; Patel, Dhruvilkumar; Mishra, Priyanka; Patil, Sneha; Sridhar, Balasubramanian; Singh, Saurabh Kumar; Pandey, Ashok Kumar (Synlett, 2025)
The first concise and convenient synthesis of natural products, antibiotics, and anticancer agents resembling cytogenin and other isocoumarins has been achieved by using three components (an N-aroyl β-amino ester, an MBH acetate, and N-bromosuccinimide) under ruthenium(II) catalysis. This method provides intermediate isochroman-1-imines through C(sp2)–H allylation with halocyclization in a single operation. Substrate scope studies, a scale-up, and density functional theory calculations to establish the mechanism of the C–H allylation were carried out.
Keywords: ruthenium catalysis; allylation; isochromanimines; isocoumarins; cytogenin analogues